Measurements of immature platelets with haematology analysers are of limited value to separate immune thrombocytopenia from bone marrow failure - Cybulska, Annalina; Meintker, Lisa; Ringwald, Juergen; Krause, Stefan (British Journal of Haematology, 2017)
Detection of immature platelets in the circulation may help to dissect thrombocytopenia due to platelet destruction from bone marrow failure (BMF). We prospectively tested the predictive value of immature platelets, measured as immature platelet fraction (IPF) on the XE-5000 (Sysmex, Kobe, Japan) or percentage of reticulated platelets (rPT) on the CD Sapphire (Abbott Diagnostics, Santa Clara, CA, USA) to separate immune thrombocytopenia (ITP) from BMF (leukaemia, myelodysplastic syndrome, aplastic anaemia). We analysed 58 samples of patients with BMF, 47 samples of patients with ITP and 97 controls. Median rPT (CD Sapphire) was increased to 9·0% in ITP and to 10·9% in BMF, compared to 1·9% in controls. Median IPF (XE-5000) was 16·2% in ITP, 10·2% in BMF and 2·5% in controls. We found an inverse correlation between high fractions of immature platelets and low platelet counts in thrombocytopenic samples regardless of the diagnosis. In conclusion, we observed a broad overlap of immature platelets between ITP and BMF, which may be caused by an accelerated release of immature platelets in any thrombocytopenic state and decreased production in many patients with ITP. Despite this, IPF (XE-5000) had some power to discriminate ITP from BMF, whereas rPT (CD Sapphire) was of no predictive value.
EVALuna2:25762